Microwave Assisted Facile Synthesis of N-doped Graphene Oxide - Rajput, Shubham (My University, 2019)
Graphene oxide (GO) described as a graphene sheet consisting of hydroxyl, epoxide, carbonyl, carboxyl functional groups. GO modifies its physical and chemical properties based on oxygen inclusions. This permits a broad range of applications. N-doped GO finds applications in energy devices such as metal-air batteries and fuel cells. In this study we synthesize the GO with modified Hummer’s method at room temperature. The formed GO was further doped with nitrogen using Urea by microwave technique using open container and Teflon Autoclave. XRD, TGA and Raman Spectroscopy indicated the successful preparation of graphene oxide and nitrogen doped-GO samples. FTIR reveals the presence of N-containing functional groups for the doped samples. DC resistivity measurements show that the conductivity is enhanced for the nitrogen doped samples with maximum conductivity for the sample synthesized in Teflon autoclave (1.66 S/m). SEM and EDX measurements were done to know the morphology and presence of elements. All the samples show flake like morphology with sharp edges with EDX confirming the presence of N in the doped-GO samples. The samples were characterized for their use for supercapacitor applications. The samples synthesized in Teflon autoclave showed multi fold enhancement in specific capacitance (147.79 F/cm2) as compared to undoped (13.82 F/cm2) and doped sample synthesized in open container (19.67 F/cm2).
M.Sc Thesis
Keywords: Graphene Oxide; N-doped Graphene Oxide; modified Hummer's Method; Microwave synthesis; Supercapacitor